2016
DOI: 10.1017/s0022149x16000353
|View full text |Cite
|
Sign up to set email alerts
|

Trematode infections of the freshwater snail Biomphalaria pfeifferi from a south-east Nigerian community with emphasis on cercariae of Schistosoma

Abstract: Knowledge of trematode infections in Biomphalaria pfeifferi from south-eastern Nigeria is scarce, due to the absence of Schistosoma mansoni infection in the region. Therefore, the present study sought to describe trematode infections in B. pfeifferi from the River Uzuru in the Nigeria Cement Factory area, Nkalagu, south-eastern Nigeria. Four hundred and sixty snails were checked for trematode infections, and mice were exposed to the Schistosoma cercariae shed from the snails. Adult worms were harvested from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
2
3
1
Order By: Relevance
“…Significant variation of Biomphalaria infection with S. mansoni was observed across the study seasons. The highest infection rate was observed during the dry season as compared to the wet season, which is in line with reports from Tanzania 56 , Sudan 43 , 57 and Nigeria 58 . High levels of open-field defecation, human-water contact activities, and stable water conditions are observed during the dry seasons of the year in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…Significant variation of Biomphalaria infection with S. mansoni was observed across the study seasons. The highest infection rate was observed during the dry season as compared to the wet season, which is in line with reports from Tanzania 56 , Sudan 43 , 57 and Nigeria 58 . High levels of open-field defecation, human-water contact activities, and stable water conditions are observed during the dry seasons of the year in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…Te infection rate of Biomphalaria by S. mansoni is higher during the hot (23.03%) and cold (20.49%) dry seasons than during the rainy season (16.72%). Similar results have been reported from Tanzania [93], Sudan [55,94], and Nigeria [95], indicating that schistosomiasisinfected B. pfeiferi molluscs were elevated during a dry season. Bekana et al [26] reported higher B. pfeiferi infection rates in Ethiopia (28.9%) after the rainy season (October to December), followed by the dry season between January and March (12.3%), while no infected snails were observed during the rainy season from June to September.…”
Section: Discussionsupporting
confidence: 86%
“…Not unexpectedly, and as reported from previous studies, Biomphalaria snails shedding other trematode cercariae were also frequently collected. [49][50][51][52] Although non-schistosome infections exceeded S. mansoni infections by a factor of 2.9, we noted no significant positive or negative associations with any of the groups of trematodes with S. mansoni infections. The three villages that yielded the most S. mansoni snail infections (PHS villages Kanyibok and Usenge and RESP Kotieno) also yielded by far the most infections with other trematodes, suggesting they are general "trematode-transmitting hotspots."…”
Section: Discussioncontrasting
confidence: 72%